Analyze the use of educational technologies in the teaching and learning processes in the middle of the pandemy of elementary education final years - Dias, Mariane Andreotti; Moura, Rosilene da Silva (Revista Coleta Científica, 2021)
This article presents an exploratory study on the reality of teachers at different levels of education, with the suspension of classroom activities caused by the COVID-19 pandemic. In times of pandemic, a new context is placed in front of the school reality, students and teachers increasingly distant physically and connected through a single possible resource, technology. The objective is to analyze the use of educational technologies in the teaching and learning processes amidst the pandemic of final year elementary education. The study is qualitative, with an analysis of the responses of 54 subjects between Elementary and High Schools, from private institutions and public education networks. The collection was carried out in the first semester of social isolation in Anápolis-GO, and the results indicate that the lack of infrastructure to carry out the activities and the weakness in the training of teachers for the use of digital technologies are the elements identified as major obstacles in the success of remote classes.